Managing uncertainty and promoting ownership over learning in D&T students using an interactive learning environment - Ehiyazaryan, Ester (Design and Technology Education: An International Journal, 2008)
This paper reports on a research study exploring the value of interactive media to enhancing creativity in Design and Technology (D&T) students. The literature review contextualises the issues of self-management and risktaking as phenomena which need to be managed and supported to ensure successful learning in D&T students. These phenomena are discussed from the point of view of both approaches to designing interactive media for learning and in the context of D&T education. An action research approach was adopted to exploring the value of interactive media in this respect. The findings of a preliminary study based on focus group interviews carried out with D&T A Level students are discussed, setting out a series of learning needs. These learning needs were derived from students’ descriptions of the issues influencing their engagement with creative work. The identified students’ learning needs were used to inform the design of an interactive learning environment, including the focus of its content on ecodesign issues, its social constructivist pedagogy and the structure of the learning interactions. This paper reports on the findings of the evaluation of the interactive learning environment which made implications for the value of interactive media to managing uncertainty and risk-taking in students. The new research findings highlighted the value of interactive media to encouraging students to engage in exploring a design context in an environment free of authoritarian control. The phenomenon of shared ownership over the learning problem emerged as a positive aspect of peer-to-peer collaboration. Finally, the role of the tutor as a facilitator of learning providing scaffolded support to the learning interactions was emphasised.